2022
DOI: 10.1007/s00432-022-03921-6
|View full text |Cite
|
Sign up to set email alerts
|

Indications of medical plants: what do medical students in Germany know? A cross-sectional study

Abstract: Background Patients use phytotherapy in addition to cancer therapy. Aiming to equip students with the knowledge necessary for a holistic treatment approach, the (German) national competence-based catalogue of educational objectives in medicine advises to include phytotherapy as part of the curriculum. Here, we evaluate if medical students know the official indication of herbal products as stated by the German Federal Institute for Drugs and Medical Devices (BfArM) for treating oral and abdominal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…or Matricaria recutita L. This incongruence in indications can not only be observed comparing written (folk medicine) indications with commonly practiced (students’) indications, but also when comparing official indication mandated by the German Federal Institute for Drugs and Medical Devices. So, if the students’ knowledge on indications is neither sufficiently based on official indications (Büntzel et al 2022 ) or, as shown here, on indications as supplied by written folk medicine, we should carefully check: What is actually the knowledgebase of this generation of future physicians? We observed only partly an overlap with written folk medicine.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…or Matricaria recutita L. This incongruence in indications can not only be observed comparing written (folk medicine) indications with commonly practiced (students’) indications, but also when comparing official indication mandated by the German Federal Institute for Drugs and Medical Devices. So, if the students’ knowledge on indications is neither sufficiently based on official indications (Büntzel et al 2022 ) or, as shown here, on indications as supplied by written folk medicine, we should carefully check: What is actually the knowledgebase of this generation of future physicians? We observed only partly an overlap with written folk medicine.…”
Section: Discussionmentioning
confidence: 98%
“…The more often a plant was mentioned, the more points a plant gained. For each symptom, we generated a 'hit list' of plants (Buentzel et al 2020;Büntzel et al 2021Büntzel et al , 2022. Then, the most often recommended plants for treating the symptoms were added to a simple questionnaire asking whether patients or medical students know of this plant (dichotomous answer "yes"/"no").…”
Section: Questionnaire and Recruitmentmentioning
confidence: 99%
“…According to the data available here, the source of knowledge in both populations studied (students as well as patients) is currently likely to be folk medicine rather than university education (15). Figure 3, on the other hand, illustrates the necessary transfer of knowledge between the two groups.…”
Section: Phytotherapy Education Of Medical Students Medicalmentioning
confidence: 92%
“…We developed a questionnaire, containing a TEMhitlist of medicinal plants against defined symptoms of abdominal discomfort. We used the algorithm already described by our group (14,15). To obtain this hitlist, we defined the relevant symptoms, and the type of remedy collections.…”
Section: Methodsmentioning
confidence: 99%